EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DITINJAU DARI KEMAMPUAN LITERASI MATEMATIKA DAN RASA INGIN TAHU PESERTA DIDIK DI SEKOLAH DASAR - Nurdin Arifin (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The transition of learning from the COVID-19 pandemic to the new normal phase at this time provides many changes that occur and must be made. In the aspect of education, it is necessary to redevelop students' abilities, namely mathematical literacy and curiosity, and in learning it is necessary to apply problem-based learning models because problem-based learning (PBL) models make students the center of learning. The research was carried out at SDN 001 North Samarinda Class IV A where this research was an experimental study with the method of 1) One-Shot Case Study, to obtain data on students' mathematical literacy abilities and 2) One-Group Pretest-Posttest Design, to obtain data on curiosity. know students. Based on the results of the research, 1) learning with problem-based learning models is effective in terms of students' mathematical literacy abilities and 2)) learning with problem-based learning models is effective in terms of students' curiosity.